Asymmetric treatment of reported pension expense and income amounts in CEO cash compensation calculations - Comprix, Joseph; Muller, Karl A. (Journal of Accounting and Economics, 2006)
We provide evidence that CEO cash compensation is relatively less sensitive to pension expense than pension income, suggesting that compensation committees shield CEO cash compensation from pension expense amounts. We also provide evidence that managers use relatively higher expected rate of return estimates when reporting pension income, suggesting that managers select income-increasing accounting estimates in response to compensation committees’ greater emphasis on pension income in CEO cash compensation determinations. Pension cost amounts represent a unique setting to examine such behavior as their effect on CEO cash compensation can be detrimental or beneficial, but arise from the same underlying economic activity.